Livestock production in central Mali: Economic characters and productivity indices for traditionally managed goats and sheep - Wilson, R.T.; Light, D.E. (Oxford University Press, 1986)
A study on the econmic characters and productivity indices of traditionally managed goats and sheep undertaken in a semi-arid, agropastoral system in central Mali. Discusses reproductive characters including litter size and parturition interval, and weight characters.